Gestational age is more important for short-term neonatal outcome than microbial invasion of the amniotic cavity or intra-amniotic inflammation in preterm prelabor rupture of membranes - Rodríguez-Trujillo, Adriano; Cobo, Teresa; Vives, Irene; Bosch, Jordi; Kacerovsky, Marian; Posadas, David E; Ángeles, Martina A; Gratacós, Eduard; Jacobsson, Bo; Palacio, Montse (Acta obstetricia et gynecologica Scandinavica, 2016)
INTRODUCTION: The aim of this study was to evaluate, in women with preterm prelabor rupture of membranes (PPROM), the impact on short-term neonatal outcome of microbial invasion of the amniotic cavity (MIAC), intra-amniotic inflammation (IAI), and the microorganisms isolated in women with MIAC, when gestational age is taken into account. MATERIAL AND METHODS: Prospective cohort study. We included women with PPROM (22.0-34.0 weeks of gestation) with available information about MIAC, IAI and short-term neonatal outcome. MIAC was defined as positive aerobic/anaerobic/genital Mycoplasma culture in amniotic fluid. Definition of IAI was based on interleukin-6 levels in amniotic fluid. Main outcome measures were Apgar score <7 at 5 min, umbilical artery pH ≤7.0, days in the neonatal intensive care unit, and composite neonatal morbidity, including any of the following: intraventricular hemorrhage grade III-IV, respiratory distress syndrome, early-onset neonatal sepsis, periventricular leukomalacia, necrotizing enterocolitis, and fetal or neonatal death. Labor was induced after 32.0 weeks if lung maturity was confirmed; and otherwise after 34.0 weeks. RESULTS: MIAC and IAI were found in 38% (72/190) and 67% (111/165), respectively. After adjustment for gestational age at delivery, no differences in short-term neonatal outcome were found between women with either MIAC or IAI, compared with the non-infection/non-inflammation ("No-MIAC/No-IAI") group. Furthermore, short-term neonatal outcome did not differ between the MIAC caused by Ureaplasma spp. group, the MIAC caused by other microorganisms group and the "No-MIAC/No-IAI" group. CONCLUSIONS: Gestational age at delivery seems to be more important for short-term neonatal outcome than MIAC or IAI in PPROM.
Keywords: novorozenec; Mycoplasma; Infant, Newborn; Intensive Care, Neonatal; microbial invasion of the amniotic cavity; logistické modely; Infant, Premature; výsledek těhotenství; Pregnancy; Humans; preterm birth; Apgar skóre; Fetal Membranes, Premature Rupture; anaerobní bakterie; gestační stáří; Female; Interleukin-6; aerobní bakterie; Bacteria, Anaerobic; Pregnancy Outcome; chorioamnionitida; lidé; Ureaplasma; intra-amniotic inflammation; short-term neonatal outcome; Infant, Premature, Diseases; Amniotic Fluid; Apgar Score; intenzivní péče o novorozence; ženské pohlaví; nemoci nedonošenců; plodová voda; Bacteria, Aerobic; těhotenství; Chorioamnionitis; preterm prelabor rupture of membranes; předčasný odtok plodové vody; prospektivní studie; novorozenec nedonošený; Logistic Models; Gestational Age; Prospective Studies